Ichthyotoxicity of ethanolic extract of Justicia extensa on behavioral and histopathological changes in Clarias gariepinus (Burchell, 1822) - Joshua Ekpenyong; Stanley Iheanacho; Francis Asuquo; Irom Okey (Environmental Chemistry and Ecotoxicology, 2022)
The effect of Justicia extensa leaf (ethanolic) extract on behavior and histopathology of Clarias gariepinus fingerling was investigated in the present study. The fish specimens were exposed to graded acute concentrations of the plant leaf extract (0.0, 4.0, 6.0, 8.0, 10.0, and 12.0 mL) for 96 h, during which time-dependent (24 h, 48 h, 72 h, 96 h) lethal concentrations of J. extensa, behavior, and histopathological changes in the gill and liver of the grouped specimens were evaluated. Based on the study findings, the respective values; 10.90, 8.60, 7.00 and 6.80 mL were obtained as the 24, 48, 72 and 96 h median lethal concentrations of J. extensa leaf extract to C. gariepinus fingerling. The study further indicate that the plant affected water quality conditions of the test media in a concentration-dependent manner, except for pH. Consequently, J. extensa elicited prominent behavioral aberrations (excessive mucus secretion, air gulping, respiratory distress, erratic swimming and vertical erection) and induced histopathological lesions in the gill (hyperplasia, erosion, fusion and disorganization of secondary lamella, desquamation and cellular degeneration) and liver (hepatic coagulative necrosis, vacuolation of parenchyma, hyperplasia, necrotic hepatocytes and hepatopancreatic tissue lysis) of C. gariepinus after 96 h exposure duration. The use of plant piscicides for fishing should be applied with caution in order to avert catastrophic events in the aquatic ecosystems.